Antioxidant activity from non-conventional beverage plant sources in Argentina - Conforti, Paula Andrea (2025)
The objective of this work is to evaluate the antioxidant activity of extracts from various ornamental and wild edible plants commonly found in urban parks. Antioxidant activities were assessed through ferric reducing antioxidant power (FRAP) and free radical scavenging assays (DPPH and ABTS) while the total phenolic content (TPC) was determined using the Folin–Ciocalteu reagent. Besides, eight commercial samples (ginger, turmeric, rosemary, thyme, rooibos, coriander, cloves, and drumstick) were analyzed under the same conditions. Clove extract exhibited the highest antioxidant activity among the commercial samples across all methods used. The study further explored the pH, color characteristics, and antioxidant capacities of all the samples. The pH values of the extracts varied from slightly acidic (6.71) to alkaline (9.51), with coriander extract showing the highest pH. The color profiles ranged from green-yellowish tones in leaf extracts to brown tones in bark and pod extracts, and reddish tones in flower extracts. Notably, Bougainvillea glabra and Callistemon citrinus exhibited particularly high antioxidant activities in the FRAP and ABTS assays, respectively. Correlation analysis revealed significant relationships between antioxidant activity and specific color parameters, particularly at absorbance wavelengths of 490 and 550 nm. These findings underscore the potential of certain ornamental and commercial plant species to enhance the nutritional and sensory qualities of functional beverages, contributing valuable insights for the development of health-promoting products in the beverage industry.